(untitled) (gjstudies, 2026)
This research investigates the relationship between the implementation methodologies of Accounting Information Systems (AIS) and the subsequent reliability of thefinancial data they produce, a linkage that remains underexplored despite its critical importance to organizational integrity and decision-making. Moving beyond conventionaltechnical evaluations of system success, this study posits that the process of implementation—specifically the sequence of module activation, the integration of legacy datavalidation protocols, and the structural alignment of the AIS with pre-existing internalcontrol frameworks—fundamentally shapes the epistemological quality of accountingdata. We develop a novel conceptual model, the Data Reliability Pathway (DRP),which frames implementation not merely as a technical installation but as a constitutive process that embeds reliability characteristics into the data generation lifecycle.The methodology employs a longitudinal, multi-case study design across four organizations undergoing AIS transitions, utilizing a mixed-methods approach that combinesqualitative process tracing of implementation decisions with quantitative analysis ofpost-implementation data anomaly rates, reconciliation discrepancies, and audit adjustment frequencies. Our findings reveal that implementations characterized by a’control-first’ module sequencing—where modules governing internal controls and datavalidation are activated prior to core transactional modules—yield significantly higherdata reliability metrics compared to traditional ’transaction-first’ approaches. Furthermore, the research identifies a previously unrecognized phenomenon: ’reliability decay’in phased rollouts, where delays between module implementations erode the integritybenefits of structured sequencing. The study concludes that AIS implementation strategy is a primary determinant of data reliability, offering a new paradigm for systemdesign that prioritizes data integrity architecture from the outset. This contributionreorients the field from a focus on system functionality and user adoption toward adeeper concern for the inherent trustworthiness of the informational output, with significant implications for practice, auditing standards, and the theoretical understandingof information systems as epistemic infrastructures.